The Analysis of PPKn Teacher Pedagogic Competency in Learning Activities at state high school 9 Sinjai, Tellulimpoe District - Jumiati Nur; Arahim Arahim; Hasrianto Hasrianto (Universitas of Muhammadiyah Makassar, 2021)
Pedagogic competence is the ability to manage student learning. The teacher must own competence because it is related to the characteristics of students seen from various aspects such as physical, moral, social, cultural, and intellectual. This implies that a teacher must master learning theories and educational learning principles because students have different characters, traits, and interests. This type of research uses qualitative research where this research is expected to explain the existing phenomena, especially those related to the pedagogic competence of Pancasila and Citizenship Education teachers. This study indicates that the pedagogical competence of PPKn teachers in SMA Negeri 9 Sinjai Kec. Tellulimpoe has a fairly good ability in mastering the characteristics of students, applying the principles of curriculum development related to the subjects being taught, mastery of learning theory using one method but using several learning methods, teachers have used technology, information, and communication in the interests of learning. Kompetensi pedagogik adalah kemampuan mengelolah pembelajaran peserta didik. kompetensi harus dimiliki guru karen berkenaan dengan karakteristik peserta didik dilihat dari berbagai aspek seperti fisik, moral, sosial, kultural, dan intelektual. Hal tersebut berimplikasi bahwa seorang guru harus mampu menguasai teori belajar dan prinsip-prinsip pembelajaranyang mendidik karena peserta didik memiliki karakter, sifat, dan interes yang berbeda. Jenis penelitian ini menggunakan kualitatif dimana penelitian ini diharapkan dapat menjelaskan fenomena yang ada terutama yang berkaitan dengan kompetensi pedagogik guru Pendidikan Pancasila dan Kewarganegaraan. Hasil penelitian ini menunjukan bahwa kompetensi pedagogik guru PPKn di SMA Negeri 9 Sinjai Kec. Tellulimpoe telah memiliki kemampuan yang cukup baik dalam menguasai karakteristik peserta didik, menerapkan prinsip-prinsip pengembangan kurikulum yang berkaitan dengan mata pelajaran yang di ampu, penguasaan teori belajar tidak hanya menggunakan satu metode saja tetapi menggunakan beberapa metode belajar, guru telah memanfaatkan teknologi, informasi dan komunikasi dalam kepentingan pembelajaran.